Corrigendum. Issue 1 (3rd May 2016) - Unknown
Tracy TL Cheung, Floor M Kroese, Bob M Fennis and Denise TD De Ridder Put a limit on it: The protective effects of scarcity heuristics when self-control is low. 2015; Vol. 2(2) 1–11 (DOI:10.1177/2055102915615046 )